Interaction of recombinant CanPIs with helicoverpa armigera gut proteases reveals their processing patterns, stability and efficiency - Mishra, Manasi; Tamhane, Vaijayanti A.; Khandelwal, Neha; Kulkarni, Mahesh J.; Gupta, Vidya S.; Giri, Ashok P. (Proteomics, 2010)
Six diverse representative Capsicum annuum (common name: hot pepper; Solanaceae) protease inhibitor genes, viz CanPI-5, -7, -13, -15, -19, and 22 comprising 1-4 inhibitory repeat domains (IRDs), were cloned and expressed in Pichia pastoris. The recombinant proteins were evaluated for their interactions with bovine trypsin, chymotrypsin, and Helicoverpa armigera gut proteases (HGP) using electrophoretic (native and denaturing) and mass spectrometric (MALDI-TOF-MS in combination with intensity fading assays) techniques. These techniques allow qualitative and semiquantitative analysis of multiple and processed IRDs of purified recombinant Capsicum annuum proteinase inhibitor (rCanPI) proteins. rCanPIs showed over 90% trypsin inhibition, varying chymotrypsin inhibition depending on the number of respective IRDs and over 60% inhibition of total HGP. rCanPI-15 that has only one IRD showed exceptionally low inhibition of these proteases. Interaction studies of rCanPIs with proteases using intensity fading-MALDI-TOF-MS revealed gradual processing of multi-IRD rCanPIs into single IRD forms by the action of HGP at the linker region, unlike their interactions with trypsin and chymotrypsin. Intensity fading-MALDI-TOF-MS assay showed that CanPI-13 and -15, possessing single IRD and expressed predominantly in stem tissue are degraded by HGP; indicating their function other than defense. In vitro and in vivo studies on rCanPI-5 and -7 showed maximum inhibition of HGP isoforms and their processed IRDs were also found to be stable in the presence of HGP. Even single amino acid variations in IRDs were found to change the HGP specificity like in the case of HGP-8 inhibited only by IRD-12. The presence of active PI in insect gut might be responsible for changed HGP profile. rCanPI-5 and -7 enhanced HGP-7, reduced HGP-4, -5, -10 expression and new protease isoforms were induced. These results signify isoform complexity in plant PIs and insect proteases.
Keywords: CanPI; H. armigera gut proteases; Intensity fading MALDI-TOF-MS; Pin-II; Plant proteomics; Plant-insect interaction

Enhanced permeation, leaf retention, and plant protease inhibitor activity with bicontinuous microemulsions - Tamhane, Vaijayanti A.; Dhaware, Deepika G.; Khandelwal, Neha; Giri, Ashok P.; Panchagnula, Venkateswarlu (Journal of Colloid and Interface Science, 2012)
Bicontinuous microemulsions (BCMEs) have excellent solubulizing properties along with low interfacial tension and aqueous content that can be controlled. In this work, water soluble plant protease inhibitor (PI), well characterized for its activity against insect pests, was incorporated into a BCME system and explored for permeation on hydrophobic leaf surfaces and protease inhibition activity. The bicontinuous nature of the microemulsion containing water:2-propanol:1-butanol (55:35:10 w/w) was characterized using conductivity and self-diffusion coefficient measurements. The PI was soluble in the water-rich bicontinuous domains, stable in the microemulsions, and protease inhibition activity was retained for a prolonged duration. The microemulsions ensured greater wettability and a wider spread of the PI on hydrophobic leaf surfaces as revealed by contact angle measurements. Significantly, trypsin inhibition activity assays of the PI recovered from the leaves after delivery from the microemulsion indicated a significant increase in the PI retention on the leaf. This BCME enabled greater leaf permeation and retention of the PI can be attributed to a temporary disruption of the waxy leaf surface followed by self-repair without causing any long term damage to the plant. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Bicontinuous microemulsion; Biopesticide; Microemulsion pesticide; protease inhibitor; Protein encapsulation; Protein permeation

Bio-physical evaluation and in vivo delivery of plant proteinase inhibitor immobilized on silica nanospheres - Khandelwal, Neha; Doke, Dhananjay S.; Khandare, Jayant J.; Jawale, Priyanka V.; Biradar, Ankush V.; Giri, Ashok P. (Colloids and Surfaces B-Biointerfaces, 2015)
Recombinant expression of Capsicum annuum proteinase inhibitors (CanPI-13) and its application via synthetic carrier for the crop protection is the prime objective of our study. Herein, we explored proteinase inhibitor peptide immobilization on silica based nanospheres and rods followed by its pH mediated release in vitro and in vivo. Initial studies suggested silica nanospheres to be a suitable candidate for peptide immobilization. Furthermore, the interactions were characterized biophysically to ascertain their conformational stability and biological activity. Interestingly, bioactive peptide loading at acidic pH on nanospheres was found to be 62% and showed 56% of peptide release at pH 10, simulating gut milieu of the target pest Helicoverpa armigera. Additionally, in vivo study demonstrated significant reduction in insect body mass (158 mg) as compared to the control insects (265 mg) on 8th day after feeding with CanPI-13 based silica nanospheres. The study confirms that peptide immobilized silica nanosphere is capable of affecting overall growth and development of the feeding insects, which is known to hamper fecundity and fertility of the insects. Our study illustrates the utility and development of peptide-nanocarrier based platform in delivering diverse biologically active complexes specific to gut pH of H. armigera. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Biodelivery; Helicovera armigera; Protein `corona'; Proteinase inhibitor; Silica nanospheres

Budding trends in integrated pest management using advanced micro- and nano-materials: challenges and perspectives - Khandelwal, Neha; Barbole, Ranjit S.; Banerjee, Shashwat S.; Chate, Govind P.; Biradar, Ankush V.; Khandare, Jayant J.; Giri, Ashok P. (Journal of Environmental Management, 2016)
One of the most vital supports to sustain human life on the planet earth is the agriculture system that has been constantly challenged in terms of yield. Crop losses due to insect pest attack even after excessive use of chemical pesticides, are major concerns for humanity and environment protection. By the virtue of unique properties possessed by micro and nano-structures, their implementation in Agri-biotechnology is largely anticipated. Hence, traditional pest management strategies are now forestalling the potential of micro and nanotechnology as an effective and viable approach to alleviate problems pertaining to pest control. These technological innovations hold promise to contribute enhanced productivity by providing novel agrochemical agents and delivery systems. Application of these systems engages to achieve: i) control release of agrochemicals, ii) site-targeted delivery of active ingredients to manage specific pests, iii) reduced pesticide use, iv) detection of chemical residues, v) pesticide degradation, vi) nucleic acid delivery and vii) to mitigate post-harvest damage. Applications of micro and nano-technology are still marginal owing to the perception of low economic returns, stringent regulatory issues involving safety assessment and public awareness over their uses. In this review, we highlight the potential application of micro and nano-materials with a major focus on effective pest management strategies including safe handling of pesticides. (C) 2016 Elsevier Ltd. All rights reserved.